Abstract 10027: Pulsatile Load, Rather Than Cardiac Power Output, for the Right Ventricle Determines the Prognosis in Heart Failure Patients - Chiba, Yasuyuki; Iwano, Hiroyuki; Motoi, Ko; Ishizaka, Suguru; Tsujinaga, Shingo; Tanemura, Asuka; Murayama, Michito; Yokoyama, Shinobu; Nakabachi, Masahiro; nishino, hisao; Okada, Kazunori; Kaga, Sanae; et al. (Circulation, 2021)
BackgroundAlthough cardiac power output (CPO), a parameter of cardiac performance, for the left ventricle (LV) is reported to be a powerful prognostic indicator in heart failure (HF), significance of the right ventricular (RV) CPO in HF has not been elucidated. On the other hand, RV pulsatile load stands for one of the prognostic markers in HF. We thus investigated the relationship of the RV CPO and pulsatile load to the outcome in HF. MethodsRight heart catheterization and echocardiography were performed in 231 HF patients (62±16 years, LV ejection fraction 42±18%). Invasive and noninvasive CPOs were calculated from mean systemic or pulmonary arterial pressures and cardiac output for the LV and RV. LV CPO was then corrected by LV mass (LV CPO/M). Pulmonary artery compliance (PAC) and the ratio of acceleration time to ejection time (AcT/ET) of the RV outflow velocity were used as parameters of RV pulsatile load. Cardiac death, HF hospitalization, ventricular arrhythmia and LVAD implantation after the examination were recorded. ResultsNoninvasive CPOs were moderately correlated with invasive ones (LVR=0.73, RVR=0.58, P <0.001 for both). During a median follow-up period of 441 days, cardiac events occurred in 57 patients. Using the cut-off of median values, lower LV CPO/M was associated with higher event rates, however, RV CPO did not discriminate the risk of future cardiac events. In contrast, higher RV pulsatile load was associated with higher event rates regardless of the level of LV CPO/M (Figure). In multivariable Cox proportional hazard analyses, echocardiographic LV CPO/M and AcT/ET both determined cardiac events independently of age, NYHA classification, LV ejection fraction and plasma brain natriuretic peptide levels. ConclusionPulsatile load, rather than CPO, for the RV was associated with cardiac events in HF. Furthermore, combination of echocardiographic LV CPO/M and AcT/ET could become a novel noninvasive prognostic indicator in HF patients.